Removal of Heavy Metals from Leachate Using Electro-Assisted Phytoremediation (EAPR) and Up-Take by Water Hyacinth (Eichornia crassipes) - Rudy Syah Putra; Febby Yulia Hastika (Indonesian Journal of Chemistry, 2018)
The garbage disposal management using landfill system produces an unpleasant odor of wastewater (i.e. leachate) which can disrupt the groundwater equilibrium in the rainy season. The combination of electro-assisted and phytoremediation which is hereinafter referred as Electro-Assisted Phytoremediation (EAPR) for removal of heavy metals from leachate has been demonstrated in a laboratory-scale experiment. A batch reactor setting was used to evaluate the potential removal and uptake of heavy metals (Fe, Cu, Cd, and Pb) concentration by water hyacinth (Eichornia crassipes) in the aquatic environment. An EAPR system was carried out for 11 d using constant voltage of 2 V. The results showed that the heavy metals concentration in the leachate decreased significantly for Cu, Fe, Cd and Pb metals from their initial concentration. The EAPR process could reduce as much as 77.8, 22, 31.6 and 30.0%, respectively for Fe, Cu, Cd, and Pb. Decreasing of heavy metals was followed by decreasing of TDS, electrical conductivity but increased DO concentration. Chlorophyll content in a treated plant with EAPR system showed that the water hyacinth could cope with the stress condition meanwhile accumulated high heavy metal concentration from the leachate.